Pregnant Women's Knowledge About Tetanus Toxoid (Tt) Immunization At Puskesmas, Seunuddon District Aceh Utara Regency - Fitri Hijri Khana; Zaituni (Jurnal Kesehatan Akimal, 2022)
One of the important programs in the health sector is the immunization program, which reduces morbidity, lost effort and death with one of the immunization programs, namely TT immunization, which has the benefit of preventing disease. The purpose of this study was to explain the knowledge of pregnant women about TT immunization in the Seunuddon area, North Aceh. Data collection techniques were carried out using primary data and secondary data. This type of investigation is descriptive. The study was carried out in July 2019 with a total of 40 respondents. The results of the study were sufficient, namely as many as 28 respondents (70%), while the decision on the sub-decision- modifying examination of pregnant women's knowledge about the definition of TT immunization was in the good group, namely 34 respondents (85%), mothers. with knowledge about the goodness of TT immunization in the good group, namely 17 respondents (42.5%), maternal knowledge about maternal gestational age to get TT immunization and immunization distance in the sufficient category 19 respondents (47.5%), knowledge about pregnant women. Regarding the side effects of TT immunization, 14 respondents (35%). ). The author hopes that the results of this study can be used to improve the socialization program and provide further information to the public about TT immunization.